2011
DOI: 10.1007/s00421-011-2181-z
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine’s effect on intermittent sprint cycling performance with different rest intervals

Abstract: The purpose of this study was to investigate the effects of caffeine ingestion on the performance of an intermittent sprint cycling test (ISCT) with different rest intervals. Fourteen males with team sport experience consumed 6 mg kg(-1) of caffeine or a placebo 60 min prior to completing two sets of an ISCT with 4-min rest intervals. Each set consisted of 12 × 4-s sprints with 20- or 90-s active recovery intervals at 60-70 rpm. Blood lactate was collected at baseline and immediately following the completion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 38 publications
3
31
0
2
Order By: Relevance
“…On arrival to the laboratory, participants were provided with a prepacked meal with an energy content of 492.75 Kcal, composed of 64% carbohydrate, 23% fat, and 13% protein. At 7:00 AM, after consuming their prepacked breakfast, participants ingested opaque gelatin capsules containing either 6 mg · kg −1 of CAF (Sigma-Aldrich, Sydney, Australia) or an equal dosage of placebo (cellulose, Holy Food, Taoyuan, Taiwan), along with 200 ml of water [16]. Participants then rested in a quiet room for 50-min prior to ingesting the carbohydrate solution drink or placebo.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On arrival to the laboratory, participants were provided with a prepacked meal with an energy content of 492.75 Kcal, composed of 64% carbohydrate, 23% fat, and 13% protein. At 7:00 AM, after consuming their prepacked breakfast, participants ingested opaque gelatin capsules containing either 6 mg · kg −1 of CAF (Sigma-Aldrich, Sydney, Australia) or an equal dosage of placebo (cellulose, Holy Food, Taoyuan, Taiwan), along with 200 ml of water [16]. Participants then rested in a quiet room for 50-min prior to ingesting the carbohydrate solution drink or placebo.…”
Section: Methodsmentioning
confidence: 99%
“…Existing data show that CAF supplementation may benefit sprint performance [12,13] and reactive agility performance [14] via various mechanisms [15]. However, one study demonstrated that caffeine was ergolytic for mean power and fatigue index during the high-intensity sprint test when a 24 × 4-s cycling sprint test with 20-s of active recovery was completed versus a 90-s active recovery between each sprint bout [16]. Numerous studies have also reported that CAF ingestion has a small or negligible effect on sprint performance [16-18] when repeated sprint tests (≤10-s) are interspersed with short rest periods (≤60-s), as well as no effect on reactive agility [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observing the above-mentioned RSE protocols, a trend that should be highlighted is the use of a relatively large recovery time (>1 min) mostly when the trial lasts for at least 30 s. During these exercises, fatigue is recorded as changes in the power output, the blood lactate concentration and the knee extension maximum voluntary contraction force [18,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a 24 s recovery has been used in protocols of 5 × 6 s (number of trials × duration of each trial) [16]; a 20 and 90 s recovery has been used in 12 × 4 s [18]; a 25, 50 and 100 s recovery in 10 × 5 s [24]; a 30 s recovery in 4 × 10 s [21], 5 × 6 s [9] and 6×6 s protocols [8]; 30 s, 1 and 5 min recovery in 10 × 10 s [27]; and a 40 s recovery in a 10×10 s protocol [17]. Moreover, longer recovery times have ranged from 1.5, 3 and 6 min in 2 × 30 s [3]; 3 min in 10 × 10 s [25]; 4 min in 3 × 30 s [32] and in 6 × 30 s protocols [20]; 5 min in 5 × 60 s [7]; and 20 min in a 3 × 30 s protocol [1].…”
Section: Introductionmentioning
confidence: 99%